Prognostic value of inflammatory and nutritional markers for hepatocellular carcinoma. Issue 25 (25th June 2021) - Xu, Yingying; Yuan, Xiuxue; Zhang, Xiaomin; Hu, Wenqing; Wang, Zehua; Yao, Longdi; Zong, Liang
Abstract : Abstract: Many clinical studies have demonstrated that the neutrophil to lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR), and Onodera's prognostic nutritional index (OPNI) are visibly involved in the prognosis of a variety of tumors. In our research, we aim to determin the prognostic impact of NLR, PLR, and OPNI for hepatocellular carcinoma (HCC). Data of hepatocellular carcinoma patients undergoing treatment in Changzhi People's Hospital between 2011 and 2017 were reviewed. 270 patients with HCC were under inclusion criteria. The optimal cut-off points of OPNI, NLR and PLR were determined by using the X-tile program. The overall survival (OS) was analyzed by Kaplan–Meier method. Multivariate analysis was performed using Cox Proportional Hazard Regression model to determine independent prognostic indicators for HCC. As revealed by Univariate and multivariate analysis, OPNI, Treatment, PLR, and BCLC Stage can be used as independent prognostic indicators for HCC. Comparing the P values and hazard ratios, we found out that the OPNI has greatest influence on prognosis in these indexes. The appropriate cut-off points of NLR, PLR, and OPNI were 2.5, 133.3, and 39.5, respectively. High score OPNI group had a better OS. In the analysis between OPNI and clinicopathological characteristics, there were differences in treatment, postoperative therapy, AST, ALBI grade, NLR and PLR between the high OPNI group and the low OPNI group, while others did not. OPNI is a straightforward and effective independent prognostic indicator for HCC.